A estrutura da taxocenose e a partição do nicho acústico entre anfíbios anuros em uma área de floresta atlântica - Simões, Cássio Rachid Meireles de Almeida (2014)
The structure of assemblages may be the result of recent events (e.g., ecological interactions or resources availability), as well as historical factors (like evolutionary events). The segregation of resources may be analyzed by morphometric, dietary, microhabitats, and even acoustical data. This thesis aims to test hypotheses related to the structure of an anuran assemblage and related niche segregation by using: (1) morphometric and ecological (dietary and microhabitat) data and (2) bioacoustical data. For the first approach, we collected data from 598 individuals, from 30 species. The results showed that the assemblage is not structured in terms of microhabitat usage. However, competition among phylogenetic related species is pronounced. Besides, the assemblage presents structure regarding dietary data. This result supports the existence of avoidance by competition within the studied assemblage. The effect of phylogenetic niche conservatism is also observed for the usage of microhabitat, and for morphometric and dietary variables. Based on that, we state that the species may coexist because they segregate their niche, at least in one dimension, and that the use of some specific niche component are related to their evolutionary history. For the second approach – using acoustical variables collected from advertisement calls – it was collected data from 15 species. The result has demonstrated that the majority of species present acoustic differences in their calls. The results support our hypothesis of acoustic niche partitioning (at least moderately), corroborating other studies which assert that the acoustical niche occupancy is species-specific.